2011
DOI: 10.1093/brain/awr175
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network functional and structural connectivity after traumatic brain injury

Abstract: Traumatic brain injury often results in cognitive impairments that limit recovery. The underlying pathophysiology of these impairments is uncertain, which restricts clinical assessment and management. Here, we use magnetic resonance imaging to test the hypotheses that: (i) traumatic brain injury results in abnormalities of functional connectivity within key cognitive networks; (ii) these changes are correlated with cognitive performance; and (iii) functional connectivity within these networks is influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
359
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(409 citation statements)
references
References 62 publications
40
359
2
1
Order By: Relevance
“…This linkage supports the assumption that ICN function is vulnerable to the effects of mTBI, considering that diffuse axonal injury (DAI) usually damages long-distance white-matter tracts that connect key brain areas (known as hubs) in these networks (Smith et al, 2003;Gentleman et al, 1995). ICN abnormalities after TBI have been widely observed in resting-state fMRI, demonstrating both increase and decrease of connectivity in a number of networks, including the default mode network (DMN) and salience network (SN) (Sharp et al, 2011;Stevens et al, 2012). Several studies have also reported that these abnormalities correlate with cognitive impairment or post-concussive symptoms (Messe et al, 2013;Caeyenberghs et al, 2014).…”
Section: Introductionmentioning
confidence: 61%
“…This linkage supports the assumption that ICN function is vulnerable to the effects of mTBI, considering that diffuse axonal injury (DAI) usually damages long-distance white-matter tracts that connect key brain areas (known as hubs) in these networks (Smith et al, 2003;Gentleman et al, 1995). ICN abnormalities after TBI have been widely observed in resting-state fMRI, demonstrating both increase and decrease of connectivity in a number of networks, including the default mode network (DMN) and salience network (SN) (Sharp et al, 2011;Stevens et al, 2012). Several studies have also reported that these abnormalities correlate with cognitive impairment or post-concussive symptoms (Messe et al, 2013;Caeyenberghs et al, 2014).…”
Section: Introductionmentioning
confidence: 61%
“…Articles were also excluded when the primary goal was to examine the influence of an intervention or drug and no initial group comparison was made affording the opportunity to examine relative group connectivity (e.g., Solé-Padullés et al, 2013). Finally, articles were excluded if no baseline comparison of connectivity was made between the clinical sample and healthy control sample (e.g., Bonnelle et al, 2012;Bonnelle et al, 2011) or the comparison was made but only based upon a specific contrast or manipulation (e.g., Palacios et al, 2012). Study inclusion was determined by thorough review of the study design and methods.…”
Section: Literature Searchmentioning
confidence: 99%
“…Diffuse axonal injury (DAI) (Smith, Meaney, & Shull, 2003) is a primary injury mechanism of TBI, and rsFC has been a promising technique to identify DAI‐induced higher‐order cognitive impairments (e.g., reasoning, decision making, and selective attention) among individuals with TBI (Sharp, Scott, & Leech, 2014). Notably, large‐scale network approaches using rsFC in TBI have effectively revealed the complex patterns of the injured brain (Han, Chapman, & Krawczyk, 2016; Mayer, Mannell, Ling, Gasparovic, & Yeo, 2011; Sharp et al., 2011). The large established literature in large‐scale networks in healthy individuals facilitates the interpretation of study findings as applied to individuals after a TBI.…”
Section: Introductionmentioning
confidence: 99%